On the economic causes of the present state of agriculture in Ireland: part two - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1849)
In this paper I propose to notice the second, third, and fourth elements of the cost of the transfer, viz: the expense of searches for incumbrances, the stamps on conveyances and searches, and the length of conveyances. I shall next explain the second class of impediments to the transfer of land, arising from the restraints on the power of alienation; and I shall lastly notice the effects of all these impediments on leasehold and other derivative interests.
Read December 18th 1848
Keywords: Land transfer; Land ownership; 314.15